Group agency the possibility, design, and status of corporate agents - List, Christian; Pettit, Philip, 1945- (Oxford : Oxford University Press, 2011)
Are companies, churches, and states genuine agents? How do we explain their behaviour? Can we treat them as accountable for their actions? List and Pettit offer arguments, grounded in work on social choice, economics, and philosophy, to show there really are group agents, over and above the individual agents who compose them.
Description based on online resource; title from PDF title page (viewed on May 11, 2011).
Includes bibliographical references and index.
Keywords: Agent (Philosophy); Social choice